Robust feedback controller in finite frequency based on H∞ performance for a variable speed wind turbine. (19th April 2021) - Berrada, Youssef; Boumhidi, Ismail
The modern wind turbine system is modelled as a flexible structure operating in the presence of wind speed turbulences. Furthermore, it's highly nonlinear and its dynamic changes rapidly with the change of wind speed. A sophisticated control system is needed to allow wind turbines to generate power in a wide variety of wind conditions. This paper investigates a system control in finite frequency based on H∞ performance in order to maximise the extracted energy from the wind while mitigating aerodynamic loads. The finite frequency approach is used to design a robust feedback control to stabilise the system when the disturbances occur in a finite frequency band due to the stochastic nature of the wind flow. The controller gains are given in terms of linear matrices inequality (LMIs) which can be solved easily using existing numerical tools. The performance of the proposed control strategy is investigated in terms of stability and robustness under variable wind speed, and illustrated by tests simulation using MATLAB® software.